Serum Calcium Level and Functional Atherosclerosis in Relation to Human T-Cell Leukemia Virus 1 Infection in Older Individuals - Yuji Shimizu; Hirotomo Yamanashi; Jun Miyata; Midori Takada; Yuko Noguchi; Yukiko Honda; Fumiaki Nonaka; Seiko Nakamichi; Yasuhiro Nagata; Takahiro Maeda (Journal of Vascular Diseases, 2023)
Serum calcium levels are known to influence vascular function. Cells infected with human T-cell leukemia virus 1 (HTLV-1) impact serum calcium levels and also affect the endothelium. Since a damaged endothelium causes functional atherosclerosis, serum calcium levels in HTLV-1 carriers may be positively associated with functional atherosclerosis. This cross-sectional study enrolled 1694 Japanese individuals aged 60 to 89 years. Functional atherosclerosis was defined as a cardio-ankle vascular index (CAVI) ≥ 9.0. Logistic regression analysis was used to evaluate the relationship between HTLV-1 carrier status and both serum calcium level and functional atherosclerosis. Even after adjusting for known confounding factors, the serum calcium level was significantly positively associated with functional atherosclerosis only in asymptomatic HTLV-1 carriers. The fully adjusted odds ratio and 95% confidence interval of functional atherosclerosis in relation to a one-standard-deviation increment of serum calcium level (0.4 mg/dL in both men and women) were 1.54 (1.18, 2.01) for HTLV-1 carriers (n = 322) and 0.99 (0.87, 1.13) for HTLV-1 non-carriers (n = 1372), respectively. The serum calcium level was positively associated with functional atherosclerosis only among older carriers of HTLV-1 infection. This finding can help effectively estimate the risk of functional atherosclerosis in asymptomatic HTLV-1 carriers.